Hepatitis C virus eradication by direct antiviral agents abates oxidative stress in patients with advanced liver fibrosis. (4th August 2020) - Salomone, Federico; Petta, Salvatore; Micek, Agnieszka; Pipitone, Rosaria Maria; Distefano, Alfio; Castruccio Castracani, Carlo; Rini, Francesca; Di Rosa, Michelino; Gardi, Concetta; Calvaruso, Vincenza; Di Marco, Vito; Li Volti, Giovanni; et al.
Abstract: Background and aims: HCV eradication improves non‐hepatic outcomes such as cardiovascular diseases, although without clearly defined mechanisms. In this study we aimed to assess whether improvement of carotid atherosclerosis may be linked to a reduction in systemic oxidative stress after viral clearance. Methods: We studied a retrospective cohort of 105 patients (age 62.4 ± 11.2 years; 62 men) with F3/F4 fibrosis, characterized by carotid ultrasonography at baseline and at sustained virologic response (SVR) follow‐up. Levels of 8‐iso‐prostaglandin F2α (F2 ‐isoprostanes) and other oxidative stress markers were measured on frozen sera. Association between change (denoted as Δ) in oxidative stress markers (exposures) and change in carotid intima‐media thickness (cIMT) (outcome) was examined using multiple linear regression. Results: Subclinical atherosclerosis, defined as the presence of carotid plaque and/or cIMT ≥ 0.9, was present in 72% of the cohort. All patients achieved SVR that led to reduction in cIMT (0.92 ± 0.20 vs 0.83 ± 0.21 mm, P  < .001). HCV eradication markedly decreased serum levels of F2 ‐isoprostanes (620.5 [143.2; 1904.1] vs 119.51 [63.2; 400.6] pg/mL, P  < .0001), lipid hydroperoxides (13.8 [6.3; 20.7] vs 4.9 [2.3; 9.6] nmol/μl, P  < .0001) and 8‐hydroxy‐2'‐deoxyguanosine (558.9 [321.0; 6301.2] vs 294.51 [215.31; 408.95] pg/mL, P  < .0001), whereas increased serum GPx activity (10.44 [4.6; 16.3] vs 13.75 [9.42; 20.63] nmol/min/mL, P  = .001). By multiple linear regression analysis ΔcIMT was independently associated with ΔF2 ‐isoprostanes (β: 1.746 [0.948; 2.543]; P  < .0001) after adjustment for age, baseline F2 ‐isoprostanes and baseline IMT. Conclusions: Besides association of lipid peroxidation with severity of liver disease, the reduction in F2 ‐isoprostanes may be involved in the improvement of atherosclerosis after HCV eradication.